The relationship between sitting height, sitting height to height ratio with blood pressure among Polokwane private school children aged 6-13 years - Nthai E. Ramoshaba; Kotsedi D. Monyeki; Joyce Mpya; Mafolwa S. Monyeki (BMC, 2018)
Abstract Background It is notable that sitting height (SH) correlates with blood pressure (BP) in children and adolescents of developed countries. However, little is known about the relationships between SH and SH to height ratio (SH/H) with BP in South African children from middle and upper socio-economic groups. The purpose of this study was to compare SH and SH/H of private school attending children in the Polokwane area with National Health and Nutrition Examination Survey III (NHANES III) reference population and to determine the relationship between SH, SH/H with BP among private school attending children. Methods A total of 1665 children (846 boys and 819 girls) aged between 6 and 13 years attending three private schools in Polokwane, underwent anthropometric and BP measurements using standard procedures. Linear regression was used to determine the relationship between height, SH, SH/H with BP among these children. Results Polokwane private school attending boys from age 7 to 13 years displayed a lower mean SH compared to the NHANES III whereas NHANHES III girls from age 10 to 13 years had a higher mean SH compared to those in private school. In the simple regression analysis, SH was positively associated with SBP (β =1.318; 95% CI = 1.217-1.418) and DBP (β = 0.641; 95% Cl = 0.555-0.727). The findings remains statistically significant only for SH with both SBP (β = 1.025; 95% Cl = 0.844-1.201) and DBP (β = 0.585; 95% Cl 0.434-0.736) after adjusting for age, gender and BMI among these children. Conclusion In South African children, SH and SH/H were lower compared to the NHANES III children. There was a significant positive association between DBP and SBP together with the components of height among Polokwane private school children.